(3MGTjI Ydi Ce GdHQGgjfs - (3GdHGLhQj, EHQGgje Hf eMeO Hf CMeO, J (B1277 (3g`s ((3eMeO QMeI Gddg CHh GdNjQ Hf GdNWjHs)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj JhMO aj PGJg hHYO ajbhd EHQGgje GdHGLhQj SCdfj HYV GdENhGf Gf CcJH cJGHI HgjI Ydi GdebOeI GdeTghQI HGdSfhSjI aGfTQM UOQj dPdc s
(3BNQgG (B:s
(3hbhdg GdMeO ddg QH GdYGdejf ajg MSf GNJJGe dCf Pdc OYGA GdeDefjf aj OGQ GdLfGf hajg GjVG GdETGQI Edi GdbHhd dCf Ve GdOYGA Hg YdGeI Ydi GLGHJgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 71s
(3eYLe GdeDdajf (B1 / 57s
(3MdjI GdHTQ (B1 / 905s
(3gOjI GdYGQajf (B1 / 41s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds